Production and characterization of a single-chain Fv antibody–alkaline phosphatase fusion protein specific for ampicillin. Issue 1 (1st January 2019) - He, Kuo; Wei, Fan; Zhang, Xiuyuan; Li, Jiayi; Zhang, Donghao; Wei, Dong
ABSTRACT: Anti-AMP scFv were prepared by cloning variable region genes (VH and VL) from hybridoma cell line which secretes antibodies against AMP, and phoA gene was cloned from Escherichia coli strain K12 chromosomal DNA. The resulting scFv and phoA gene were inserted into the expression vector pBV220 to express the scFv–AP fusion protein in E. coli strain BL21. The puriﬁed scFv-AP fusion protein was used to develop an ic-CLEIA method for detection of AMP. The limit of detection (IC15 ) was 0.11 ± 0.004 ng/mL and the IC50 was 0.75 ± 0.04 ng/mL, respectively. The assay was 3 times as sensitive as the corresponding ic-ELISA based on the same fusion protein. IC-CLEIA was used to analyse AMP spiked milk samples, and the validation was conﬁrmed by HPLC. Good correlation between ic-CLEIA and HPLC data was obtained ( R 2 = 0.9934). It indicated that the developed method can apply to effectively monitor food safety.